2014
DOI: 10.1007/s10570-014-0431-z
|View full text |Cite
|
Sign up to set email alerts
|

Structure and spacing of cellulose microfibrils in woody cell walls of dicots

Abstract: There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/105070/ Key words: WAXS; WANS; SANS; crystallinity; Scherrer; wood AbstractThe structure of cellulose microfibrils in situ in wood from the dicotyledonous (hardwood) species cherry and birch, and the vascular tissue from sunflower stems, was examined by wide-angle X-ray and neutron scattering (WAXS and WANS) and small-angle neutron scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
49
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 20 publications
15
49
1
Order By: Relevance
“…In secondary cell walls of dicots, small-angle neutron scattering studies indicated that the microfibrils were around 4 nm wide [34,43], exceeding the ca 3 nm width consistent with an 18chain structure ( figure 3). The small-angle scattering experiments required deuterium exchange at the interface to generate contrast [34], so the dimension concerned is probably across the hydrophilic faces of the microfibrils. The extra width has been attributed to interpolation of a xylan chain [34], fusion of the microfibrils over part of their length [34], or interpolation of bound water [43].…”
Section: Microfibrils Can Be Enlarged By Fusion or By Accretion Of Hementioning
confidence: 98%
See 1 more Smart Citation
“…In secondary cell walls of dicots, small-angle neutron scattering studies indicated that the microfibrils were around 4 nm wide [34,43], exceeding the ca 3 nm width consistent with an 18chain structure ( figure 3). The small-angle scattering experiments required deuterium exchange at the interface to generate contrast [34], so the dimension concerned is probably across the hydrophilic faces of the microfibrils. The extra width has been attributed to interpolation of a xylan chain [34], fusion of the microfibrils over part of their length [34], or interpolation of bound water [43].…”
Section: Microfibrils Can Be Enlarged By Fusion or By Accretion Of Hementioning
confidence: 98%
“…This contention is based on spindiffusion NMR experiments, indicating that the spatial separation between these two forms is less than the width of a microfibril, not tens of nanometres as required by the alternating model. Also, the alternating model requires an assumption that the disordered segments of the microfibril have an open structure permeable to water, to explain the observation that their hydroxyl protons exchange with D 2 O; but deuteration-wide-angle neutron scattering experiments showed that the spacing of the deuterated chains was no greater than in crystalline cellulose [10,34], consistent with these chains being located at a solid surface. The proportion of crystalline, C6-tg chains increases to 60% or more in celluloses like flax and cotton whose larger diameter gives them a smaller surface-to-volume ratio [29].…”
Section: Chains Of Different Types Have Characteristic Locations Withmentioning
confidence: 99%
“…In vascular plants, both water-conducting tracheary elements and supportive fibers are characterized by helical (Barnett and Bonham, 2004) and aggregated (Donaldson, 2007;Fernandes et al, 2011;Thomas et al, 2014) cellulose microfibrils. The midribs of P. patens leaves include hydroid cells that transport water and stereid cells that provide support, but only the stereids have thick cell walls (Xu et al, 2014).…”
Section: Secondary Cell Wall Microfibrillar Texture Is Similar In Mosmentioning
confidence: 99%
“…Secondary cell walls of water-conducting tracheary elements and supportive fibers are rich in cellulose, with microfibrils arranged in helices that vary in angle according to developmental stage and environmental conditions (Barnett and Bonham, 2004). Secondary cell wall microfibrils also are more aggregated than those of primary cell walls (Donaldson, 2007;Fernandes et al, 2011;Thomas et al, 2014). Recently, sum frequency generation (SFG) spectroscopy has been used to compare the mesoscale structure of cellulose microfibrils in primary and secondary cell walls.…”
mentioning
confidence: 99%
See 1 more Smart Citation